2004
DOI: 10.1038/sj.bjc.6601887
|View full text |Cite
|
Sign up to set email alerts
|

High levels of untreated distress and fatigue in cancer patients

Abstract: The purpose of the study was to assess a large representative sample of cancer patients on distress levels, common psychosocial problems, and awareness and use of psychosocial support services. A total of 3095 patients were assessed over a 4-week period with the Brief Symptom Inventory-18 (BSI-18), a common problems checklist, and on awareness and use of psychosocial resources. Full data was available on 2776 patients. On average, patients were 60 years old, Caucasian (78.3%), and middle class. Approximately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
605
12
32

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(715 citation statements)
references
References 35 publications
48
605
12
32
Order By: Relevance
“…A further limitation of the study is that patients were asked to rate symptoms over the last week or 2 weeks depending on the tool used. Patients may prefer different sources of help at different points in their treatment [5,29]. For example, individual counselling was viewed as being useful for coping with distress during the course of treatment, but couple counselling may be more helpful for dealing with the effects of illness on other relationships once the acute treatment has ended [29].…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation of the study is that patients were asked to rate symptoms over the last week or 2 weeks depending on the tool used. Patients may prefer different sources of help at different points in their treatment [5,29]. For example, individual counselling was viewed as being useful for coping with distress during the course of treatment, but couple counselling may be more helpful for dealing with the effects of illness on other relationships once the acute treatment has ended [29].…”
Section: Discussionmentioning
confidence: 99%
“…These standardized questions included their current medical condition, adherence with the walking program, the amount and type of exercise performed, their current FVAS and PVAS rating, chemotherapy or radiation therapy being received, and the presence or absence of the following 10 symptoms: fatigue, pain, shortness of breath, weight loss, anorexia, diarrhea, constipation, weakness, insomnia, and depression. This 10 symptom profile survey was based on a literature review of the most commonly reported symptoms in patients with PPC (6,11,(12)(13)(14)(15)(24)(25)(26)(27), and was administered to the IG during monthly follow-up phone calls and upon final follow-up. The UCG received the followup 10 symptom profile survey only upon final follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…For example, when 600 postings from pancreas cancer patients and their families in a monitored Internet pancreas cancer Frequently Asked Questions chat room were analyzedpain, fatigue, and anorexia were the most frequently reported symptoms by post-operative patients as well as those who did not have surgery (11). Other investigations have reported fatigue, pain, weight loss, nausea, anorexia, constipation, diarrhea, insomnia, depression, and anxiety as the most prevalent symptoms reported by PPC patients at all stages of disease (6,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…the HADS [19], the Hornheide Questionnaire [20,21], the Stress Index RadioOncology (SIRO, [22]), the Distress Thermometer [23,24], the PsychooncologicalBasic Documentation (PO-Bado, [25]), the Brief Symptom Inventory (BSI, [26,27]), the SymptomChecklist-90-R (SCL-90-R, [28,29]) and the GHQ-12.…”
Section: Introductionmentioning
confidence: 99%